2017
DOI: 10.1074/jbc.m117.802736
|View full text |Cite
|
Sign up to set email alerts
|

A retractable lid in lecithin:cholesterol acyltransferase provides a structural mechanism for activation by apolipoprotein A-I

Abstract: Lecithin:cholesterol acyltransferase (LCAT) plays a key role in reverse cholesterol transport by transferring an acyl group from phosphatidylcholine to cholesterol, promoting the maturation of high-density lipoproteins (HDL) from discoidal to spherical particles. LCAT is activated through an unknown mechanism by apolipoprotein A-I (apoA-I) and other mimetic peptides that form a belt around HDL. Here, we report the crystal structure of LCAT with an extended lid that blocks access to the active site, consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 63 publications
(75 reference statements)
7
60
0
Order By: Relevance
“…The simulation results showed that the lid-region of LCAT forms a coil secondary structure accompanied with relatively high residual fluctuations when compared to the other structural parts of LCAT. The fact that the lid regions are partly missing from the X-ray structures of LCAT is backing our simulation results showing a highly mobile region with no definite structural conformation (Ruwanthi N. Manthei et al, 2017; Derek E. . Another important finding was that the highly dynamical lid-loop shields the non-polar amino acids located at the tunnel opening from the water.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The simulation results showed that the lid-region of LCAT forms a coil secondary structure accompanied with relatively high residual fluctuations when compared to the other structural parts of LCAT. The fact that the lid regions are partly missing from the X-ray structures of LCAT is backing our simulation results showing a highly mobile region with no definite structural conformation (Ruwanthi N. Manthei et al, 2017; Derek E. . Another important finding was that the highly dynamical lid-loop shields the non-polar amino acids located at the tunnel opening from the water.…”
Section: Discussionsupporting
confidence: 78%
“…In this fashion, we strived to establish mechanistic insights to the conformational switching of the lid-loop that, presumably, is a prerequisite for the esterification reaction of LCAT to take place. Moreover, the overall stability of the LCAT structure was assessed against the X-ray structures to validate our computational models (Ruwanthi N. Manthei et al, 2017;Derek E Piper et al, 2015). To construct applicable LCAT models for these purposes, the lid loop region (aa 233-247) was computationally grafted to the high resolution X-ray structures of LCAT representing either the open or closed state (Ruwanthi N. Derek E. Piper et al, 2015).…”
Section: The Flexible Lid-loop Covers Non-polar Amino Acids Located Amentioning
confidence: 99%
See 1 more Smart Citation
“…rhLCAT Treatment of Mice. rhLCAT (MEDI6012) was produced as previously described (Manthei et al, 2017). Human and mouse LCAT enzymes possess a high degree of homology (Peelman et al, 1999), and indeed we found 87% identity between human and mouse LCAT reference protein sequences by BLAST analysis.…”
Section: Methodssupporting
confidence: 64%
“…A critical participant herein is the ATP-binding cassette A1 (ABCA1) expressed on liver cells and enterocytes. These nascent, discoidal apoA-I containing HDL particles are secreted via hepatic and enterocyte ABCA1 and are matured in circulation via the lecithine-cholesterolacyltransferase (LCAT) function and formation of spherical HDL particles [24]. In the absence of ABCA1, extremely low levels of HDLc and apoA-I are observed, which contribute to an increased risk for CVD.…”
Section: Introductionmentioning
confidence: 99%